Urban Catholic High Schools and Disadvantaged Females - Merrit, Corinne R. (Catholic Education: A Journal of Inquiry and Practice, 2008)
The purpose of this study was to discover the life experiences of disadvantaged female graduates of urban Catholic high schools and what they say about the capacity of Catholic education to meet their academic, emotional, social, and spiritual needs. Based on narrative inquiry, this study was conducted using a series of in-depth, semistructured interviews to elicit the life experiences of 5 participants. Twelve common personal characteristics emerged directly from the narratives of the participants and provided the backdrop for two patterns: (a) the importance of education, and (b) the importance of relationships. This study found the high school experiences met the academic needs of all participants, but the different school sites varied in their ability to meet the emotional, social, and spiritual needs. This study also found four characteristics interacted in creating the Catholic school culture: (a) building relationships, (b) promoting a sense of community, (c) supporting a caring and nurturing environment, and (d) emphasizing respect for all members of the school community.